2023
DOI: 10.1017/jfm.2023.316
|View full text |Cite
|
Sign up to set email alerts
|

The response of small-scale shear layers to perturbations in turbulence

Abstract: The perturbation response of small-scale shear layers in turbulence is investigated with direct numerical simulations (DNS). The analysis of shear layers in isotropic turbulence suggests that the typical layer thickness is about four times the Kolmogorov scale $\eta$ . Response for sinusoidal perturbations is investigated for an isolated shear layer, which models a mean flow around the shear layers in turbulence. The vortex formation in the shear layer is optimally promoted by the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 104 publications
2
14
0
Order By: Relevance
“…2020 b ). Recent studies of small-scale shear layers confirmed the optimal wavelength for the small-scale shear instability, which is approximately 30 times the Kolmogorov scale (Watanabe & Nagata 2023). When turbulence is subject to perturbations of this wavelength, the shear layers promptly collapse, resulting in a higher population of vortices arising from the shear instability.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…2020 b ). Recent studies of small-scale shear layers confirmed the optimal wavelength for the small-scale shear instability, which is approximately 30 times the Kolmogorov scale (Watanabe & Nagata 2023). When turbulence is subject to perturbations of this wavelength, the shear layers promptly collapse, resulting in a higher population of vortices arising from the shear instability.…”
Section: Introductionmentioning
confidence: 94%
“…The perturbed velocity field is formulated as . A prior study addressed the impacts of on small-scale shear instability in HIT, where the changes due to the promoted instability were discussed in terms of the number of vortices, energy dissipation, enstrophy production and strain self-amplification (Watanabe & Nagata 2023). Adopting this same methodology, is described using sinusoidal functions: , where is the amplitude, and is the wavelength.…”
Section: The Dns Of a Turbulent Front Evolving Into A Non-turbulent F...mentioning
confidence: 99%
See 3 more Smart Citations